2022
DOI: 10.3390/nu14040747
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Probiotics, Resistant Starch, and Resistant Proteins in Ameliorating Inflammation during Aging (Inflammaging)

Abstract: Aging is typically accompanied by biological and physiological changes that alter cellular functions. Two of the most predominant phenomena in aging include chronic low-grade inflammation (inflammaging) and changes in the gut microbiota composition (dysbiosis). Although a direct causal relationship has not been established, many studies have reported significant reductions in inflammation during aging through well-maintained gut health and microbial balance. Prebiotics and probiotics are known to support gut h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 118 publications
0
33
0
3
Order By: Relevance
“…In an animal model of NAFLD, decreased abundance of Akkermansia muciniphila was observed ( 40 ). It was also found that A. muciniphila prevents fatty liver disease by regulating the expression of genes that regulate fat synthesis and inflammation in the liver ( 41 ). Moreover, a recent human study showed that the intake of RSs promotes the abundance of A. muciniphila ( 42 ).…”
Section: Potential Mechanisms Of Resistant Starches On Regulating The...mentioning
confidence: 99%
“…In an animal model of NAFLD, decreased abundance of Akkermansia muciniphila was observed ( 40 ). It was also found that A. muciniphila prevents fatty liver disease by regulating the expression of genes that regulate fat synthesis and inflammation in the liver ( 41 ). Moreover, a recent human study showed that the intake of RSs promotes the abundance of A. muciniphila ( 42 ).…”
Section: Potential Mechanisms Of Resistant Starches On Regulating The...mentioning
confidence: 99%
“…High IL-1ÎČ and TNF-α levels upregulate proteolytic enzymes, such as MMPs and ADAMTS family, which degrade the extracellular matrix [ 9 , 11 ]. Probiotics are well recognized for their anti-inflammatory properties [ 38 , 39 ] and previous research has highlighted the IL-1ÎČ and TNF-α cytokines as important targets in probiotic treatment strategies for arthritic diseases [ 19 , 40 ]. In particular, consumption of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant starch in foods influences a variety of physiological activities and has been linked to a variety of health effects. Some established health benefits include lower energy content, hypocholesterolemic activities, and anti-colorectal cancer protection 33 . Studies on the influence of dietary resistive content on glucose response have yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%